AB0545 Assessment of Left Ventricular Function in Systemic Lupus Erythematosus Patients by Speckle Tracking Echocardiography: Relation to Circulating Endothelial Progenitor Cells. (9th June 2015) - Alnaggar, A.R.; Bakhoum, S.W.G.; Elbasel, M.; Hussein, H.; Hamdy, M.S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a typical systemic autoimmune disease associated with endothelial dysfunction that leads to accelerated atherosclerosis. Endothelial progenitor cells (EPCs) responsible for vascular regeneration were shown to have reduced number and impaired function in SLE. Abnormalities of left ventricular (LV) systolic and diastolic function and increased LV mass have been described in SLE patients. Endothelial dysfunction and EPCs mobilization abnormalities in SLE contribution to this LV dysfunction is uncertain. Objectives: The aim of this study was to assess left ventricular (LV) diastolic and systolic function of SLE patients using the relatively new speckle tracking echocardiography (STE) and examine whether any detected abnormalities of LV function have any relation with peripheral circulating EPCs count. Methods: 50 SLE patients without clinical evidence of cardiac involvement or cardiovascular risk factors and 25 healthy age and sex matched controls were subjected to quantification of peripheral circulating VEGFR2 + /CD133 + and VEGFR2 + /CD34 + EPCs using flow cytometry technique, conventional transthoracic echocardiography (TTE), tissue Doppler imaging (TDI) and STE. Results: Patients showed a significantly lower CD133 + /VEGFR2 + EPCs (p=0.009) and CD34 + /VEGFR2 + EPCs counts (p=0.0001) compared to controls. TTE/TDI revealed a significantly lower LV ejection fraction (LVEF) (p=0.007), higher LV end systolic dimensions (p=0.02), myocardial performance index (p=0.0001) and mitral flow E/lateral annulus E' ratio (p=0.002) in patients compared to controls. STE showed a significantly lower global longitudinal strain (p value <0.001), global circumferential strain (GCS) (p<0.001) and global strain rate during isovolumic relaxation period (GSRIVR ) (p=0.01) in patients compared to controls. By multiple logistic regression analysis, the independent variables affecting GCS and GSRivr were the prednisolone dose and the LVEF respectively. (95% CI = -0.465 to -0.027; p=0.028 and 95% CI =0.001 to 0.01; p=0.021; respectively). Conclusions: TDI and STE detected subclinical systolic and diastolic abnormalities of LV function in SLE patients. The significantly lower EPCs count detected in patients did not however have any impact on these abnormalities of LV function. References: Urowitz MB, Bookman AA, Koehler BE, et al. the bimodal mortality pattern of systemic lupus erythematosus. Am J Med 1976; 60:221-5. Ebner P, Picard F, Richter J, et al. accumulation of VEGFR2+/CD133+ cells and decreased number and impaired functionality of VEGFR2+/CD34+ cells in patients with SLE. Rheumatology 2010; 49:63-72. Paran D, Caspi D, Levartovsky D, et al. cardiac dysfunction in patients with systemic lupus erythematosus and antiphospholipid syndrome. Ann Rheum Dis 2007; 66: 506-10. Geyer H, Caracciolo G, Abe H, et al. assessment of myocardial mechanics using speckle tracking echocardiography: fundamentals and clinical applications. J Am Soc Echocardiogr 2010; 23: 351-69. Disclosure of Interest: None declared